AGENSI PEREMPUAN DIFABEL BERDAYA DALAM MENGHADAPI DISKRIMINASI GANDA DI RUANG PUBLIK - Wardatullah Sultan; Siti Luthfiah; Ulil Albab; Syamraeni; Mudfainna (Smart Education, 2026)
Abstract: Women with disabilities continue to experience multiple forms of discrimination in public spaces resulting from the intersection of gender and disability. This condition often positions women with disabilities as vulnerable and socially perceived as lacking agency. However, empirical realities show that some women with disabilities actively exercise agency in responding to such discrimination. This study aims to analyze the forms of multiple discrimination experienced by women with disabilities in public spaces and to examine how their agency is constructed and practiced in facing these challenges. This research employs a qualitative descriptive-analytical approach. Data were collected through in-depth interviews with three empowered women with disabilities who are actively engaged in public spaces, supported by limited observation. Data analysis was conducted using thematic analysis based on the Miles and Huberman model. The findings indicate that multiple discrimination manifests in symbolic exclusion, paternalistic treatment, and doubts about women’s capacities. Nevertheless, women with disabilities develop agency through family support, education, social and organizational networks, and professional positions. Their agency is expressed through strategies of capacity demonstration, identity negotiation, critical adaptation, and collective agency strengthening. This study emphasizes that women with disabilities should not be viewed as passive subjects but as active social actors capable of navigating and challenging discrimination in public spaces. Keywords: Women With Disabilities, Double Discrimination, Agency, Public Space. Abstrak: Perempuan penyandang disabilitas masih menghadapi diskriminasi ganda di ruang publik yang bersumber dari persilangan identitas gender dan disabilitas. Kondisi ini sering kali menempatkan perempuan difabel pada posisi rentan dan dipersepsikan tidak berdaya. Namun, dalam praktik sosial, sebagian perempuan difabel justru menunjukkan kapasitas agensi yang aktif dalam menghadapi berbagai bentuk diskriminasi tersebut. Penelitian ini bertujuan untuk menganalisis bentuk diskriminasi ganda yang dialami perempuan difabel di ruang publik serta mengkaji bagaimana agensi perempuan difabel berdaya dibangun dan dijalankan dalam menghadapi diskriminasi tersebut. Penelitian ini menggunakan pendekatan kualitatif dengan jenis deskriptif-analitis. Data diperoleh melalui wawancara mendalam dengan tiga perempuan difabel berdaya yang aktif di ruang publik, serta dilengkapi dengan observasi ringan. Analisis data dilakukan menggunakan analisis tematik dengan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa diskriminasi ganda dialami dalam bentuk diskriminasi simbolik, perlakuan paternalistik, dan keraguan terhadap kapasitas perempuan difabel. Meskipun demikian, perempuan difabel membangun agensi melalui dukungan keluarga, pendidikan, jaringan sosial dan organisasi, serta posisi profesional. Agensi tersebut diwujudkan melalui strategi pembuktian kapasitas, negosiasi identitas, adaptasi kritis, dan penguatan agensi kolektif. Penelitian ini menegaskan bahwa perempuan difabel bukan subjek pasif, melainkan aktor sosial yang berdaya dalam menghadapi diskriminasi di ruang publik. Kata Kunci: Perempuan Difabel, Diskriminasi Ganda, Agensi, Ruang Publik